1996
DOI: 10.1021/es9603867
|View full text |Cite
|
Sign up to set email alerts
|

Corrinoid-Mediated Reduction of Tetrachloroethene, Trichloroethene, and Trichlorofluoroethene in Homogeneous Aqueous Solution:  Reaction Kinetics and Reaction Mechanisms

Abstract: It is shown that in homogeneous aqueous solution containing titanium(III) citrate or titanium(III)-NTA as bulk electron donor, cobalamin, cobinamide, and cobamide are effective electron transfer mediators for the reduction of tetrachloroethene (PCE), trichloroethene (TCE), and trichlorofluoroethene (TCFE). For a given chlorinated ethene, the reaction rate varied only slightly with pH and type of corrinoid present and was about 5 and 50 times faster for PCE as compared to TCFE and TCE, respectively. Evidence is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
235
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(258 citation statements)
references
References 51 publications
21
235
2
Order By: Relevance
“…Recent studies pointed out that radical intermediates are involved in reductive dechlorination with cobalamin as model system [15,17]. The behaviour of chlorovinyl-radical species was investigated in the computational study by Nonnenberg et al [20].…”
Section: Compound-specific and Position-specific Chlorine Isotope Effmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies pointed out that radical intermediates are involved in reductive dechlorination with cobalamin as model system [15,17]. The behaviour of chlorovinyl-radical species was investigated in the computational study by Nonnenberg et al [20].…”
Section: Compound-specific and Position-specific Chlorine Isotope Effmentioning
confidence: 99%
“…It is unclear whether the underlying dehalogenation reaction involves nucleophilic addition by Co(I), nucleophilic substitution by Co(I) or a radical mechanism involving a single electron transfer (SET) step from Co(I) to the organohalide (Scheme 2) [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Photoreversible inactivation of PCE reduction in cell extracts by 1-iodopropane indicated that a cob(I)amid is involved in the catalysis of this reductive dechlorination reaction (21,25,29,34,41,42). Cob(I)alamin in its free form has previously been shown to reductively dechlorinate PCE and other chlorinated ethenes in homogeneous aqueous solutions (7,11). It has been suggested that the first step of PCE reduction by cob(I)alamin is a dissociative oneelectron transfer that yields a vinyl radical and cob(II)alamin (11).…”
mentioning
confidence: 99%
“…Cob(I)alamin in its free form has previously been shown to reductively dechlorinate PCE and other chlorinated ethenes in homogeneous aqueous solutions (7,11). It has been suggested that the first step of PCE reduction by cob(I)alamin is a dissociative oneelectron transfer that yields a vinyl radical and cob(II)alamin (11). Several chloroethene RDases have been purified and characterized (18,22,27,29,34,41,42).…”
mentioning
confidence: 99%
“…Hence, in the presence of dechlorinating bacteria, the presence of a chlorinated solvent represents oxidative power. Highly reduced anaerobic environments, (indicated by a low redox potential) typical for methanogenesis, have been found to be a requisite for the reductive dechlorination of halogenated compounds (i.e., the substitution of halogen atoms by hydrogen atoms) (Stuart et al, 1999 (Ensley, 1991, Furukawa et al, 2005, Burris et al, 1996, Gantzer and Wackett, 1991, Glod et al, 1997and Jablonski and Ferry, 1992. These reactions have been reported to occur cometabolically or coupled to energy generating reactions where PCE serves as an electron acceptor (Fathepure et al, 1987, Gerritse et al, 1996and Holliger et al, 1993.…”
Section: Introductionmentioning
confidence: 99%